The impact of oral disorders on the adults of Barangay 883, Sta. Ana Manila - Lim, Joanne Myrtel
Oral Health disorders have significant impact on every individual's life. The role performance and functional capabilities of an individual are affected. These oral health problems have economic consequences which includes costs of services, time factor and effect on productivity level. The consequences act as burden that is more felt by those individuals with lesser resources. The researchers' intent was to estimate the burden of oral diseases among the adults in terms of cost, time and productivity. The subjects were taken from one block out of four of Barangay 883, Sta. Ana, Manila wherein the UPCD Community Dentistry Department is holding their project. A participation rate of 89% was achieved in the study. The subjects were interviewed and were asked to answer a survey questionnaire. Results showed that 85% experienced oral disorders within the past year but only 72.41% sought care. Care from private practitioners was the most sought with 73.81%. Pain and presence of cavities were the most frequent problems encountered with 60.34%. For the mean cost spent for treatment per person is 1036.32. The mean time spent for treatment per visit is 52.9 minutes. For their productivity level, 53.45% reported having difficulty doing their usual jobs or chores and 48.28% were unable to function. With that, oral health disorders affect the quality of life of the adults of Baranaav 883. Sta. Ana. Manila. Eventhouqh thev belong to the urban poor of the community, thev still seek and find time to access and avail treatment for their ailment.